3b+8-(b+2)=4b+14-(2b+8)

Simple and best practice solution for 3b+8-(b+2)=4b+14-(2b+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3b+8-(b+2)=4b+14-(2b+8) equation:


Simplifying
3b + 8 + -1(b + 2) = 4b + 14 + -1(2b + 8)

Reorder the terms:
3b + 8 + -1(2 + b) = 4b + 14 + -1(2b + 8)
3b + 8 + (2 * -1 + b * -1) = 4b + 14 + -1(2b + 8)
3b + 8 + (-2 + -1b) = 4b + 14 + -1(2b + 8)

Reorder the terms:
8 + -2 + 3b + -1b = 4b + 14 + -1(2b + 8)

Combine like terms: 8 + -2 = 6
6 + 3b + -1b = 4b + 14 + -1(2b + 8)

Combine like terms: 3b + -1b = 2b
6 + 2b = 4b + 14 + -1(2b + 8)

Reorder the terms:
6 + 2b = 4b + 14 + -1(8 + 2b)
6 + 2b = 4b + 14 + (8 * -1 + 2b * -1)
6 + 2b = 4b + 14 + (-8 + -2b)

Reorder the terms:
6 + 2b = 14 + -8 + 4b + -2b

Combine like terms: 14 + -8 = 6
6 + 2b = 6 + 4b + -2b

Combine like terms: 4b + -2b = 2b
6 + 2b = 6 + 2b

Add '-6' to each side of the equation.
6 + -6 + 2b = 6 + -6 + 2b

Combine like terms: 6 + -6 = 0
0 + 2b = 6 + -6 + 2b
2b = 6 + -6 + 2b

Combine like terms: 6 + -6 = 0
2b = 0 + 2b
2b = 2b

Add '-2b' to each side of the equation.
2b + -2b = 2b + -2b

Combine like terms: 2b + -2b = 0
0 = 2b + -2b

Combine like terms: 2b + -2b = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| x=2+8(x-12) | | 2s^2=5s-12 | | 2+2x+x=-25 | | 3x+7x=16+9x | | 2a+3-8=5a+12-3a | | 7x=-23 | | 5t+10=10t+60 | | 0.2(x+30)-0.6(x-20)=10 | | 3x+7x=x-6 | | 6.4s+3.3=12.5 | | 44=30-2(x-2) | | 2x+8=4x-(10-4x) | | 10x-(7x-5)=11 | | 4u-8=5(1-u) | | x^4-8x^3+15x^2+4x=20 | | 4x-9x+50=2x+36 | | 15=-8+x | | 4(3x+5)-2(4x-3)= | | x^4-8x^3+15x^2+4x-20=0 | | 4.2=c/0.7 | | c-10=-22 | | 4a-16=a-5 | | 16-n/8=-6 | | -2x-9=11+3x | | 21x^2-18x-5=0 | | 7x+3=24+4x | | 8x^3+x^2-55x+42=0 | | x^5-3x^4+10=0 | | 2x^3-6x+3=0 | | -32-3x=5x-37 | | 2=x^2-8+5 | | 1+2x^2-x^4=0 |

Equations solver categories